Resistance of Frozen Soils to Triaxial Compression (Soprotivlenie Merzlykh Gruntov Trekhosnomu Szhatiyu) - Vyalov,S. S.; Shusherina,E. P. (1970)
A constant obstacle to building in northern climates is the presence of permafrost, or permanently frozen earth, which introduces a large element of uncertainty into the laying of foundations for new structures. The regularities in the strain and resistance of frozen soil to loads with allowance for time in the simple forms of tests (compression, expansion, sheer) at the present time have been relatively well studied. However, it should be taken into account that the frozen soils, just as most of the unfrozen soils, possess 'friction,' more exactly the ability to increase their resistance to shear under the effect of normal stress, which also should be taken into account in the determination of the rheological parameters. Therefore, in order to best study the mechanical properties of frozen soils, it is necessary to conduct tests during a complex stressed state, when the soil is influenced by a combination of stress components. (Author) Trans. of Merzlotnye Issledovaniya (USSR) n4 p340-375 1964.